2017
DOI: 10.1371/journal.pone.0183743
|View full text |Cite
|
Sign up to set email alerts
|

NTFP harvesters as citizen scientists: Validating traditional and crowdsourced knowledge on seed production of Brazil nut trees in the Peruvian Amazon

Abstract: Understanding the factors that underlie the production of non-timber forest products (NTFPs), as well as regularly monitoring production levels, are key to allow sustainability assessments of NTFP extractive economies. Brazil nut (Bertholletia excelsa, Lecythidaceae) seed harvesting from natural forests is one of the cornerstone NTFP economies in Amazonia. In the Peruvian Amazon it is organized in a concession system. Drawing on seed production estimates of >135,000 individual Brazil nut trees from >400 conces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
(60 reference statements)
2
22
0
2
Order By: Relevance
“…With respect to the most important predictors that control its spatial distribution, our results are similar to those found in other studies. In Peru, seed production was found to be positively correlated with clay content and negatively with sand content (Thomas et al, ). In Brazil, Guerreiro et al () found that the species has a preference soils with a clayey to very clayey texture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the most important predictors that control its spatial distribution, our results are similar to those found in other studies. In Peru, seed production was found to be positively correlated with clay content and negatively with sand content (Thomas et al, ). In Brazil, Guerreiro et al () found that the species has a preference soils with a clayey to very clayey texture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our model indicates that many lowland areas were suitable in contrast to the prevailing notion that this species prefers upland areas (Scoles et al, ). Indeed, species seed production has been shown to be lower when trees were close to rivers (Thomas et al, ). The unexpected inclusion of lowland areas as suitable Amazon‐nut habitat was discussed with experts.…”
Section: Discussionmentioning
confidence: 99%
“…8), our results are similar to those found in other studies. In Peru, seed production was found to be positively correlated with clay content and negatively with sand content (Thomas et al 2017).…”
Section: Amazon-nut Habitat Suitabilitymentioning
confidence: 99%
“…excelsa has been shown to be lower when trees were close to rivers (Thomas, et al 2017). The unexpected inclusion of lowland areas as suitable Amazon-nut habitat was discussed with experts.…”
Section: Amazon-nut Habitat Suitabilitymentioning
confidence: 99%
See 1 more Smart Citation